PERSEPSI MASYARAKAT KAMPUNG BENDA KEREP TERHADAP PEMBERIAN IMUNISASI DASAR PADA ANAK - Wahyuni, Santi; G Matsuoka, Chorina; Rahayu, Tiara Destya; Fitrianingsih, Ade (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2023)
Background: Immunization coverage for babies in Benda Kerep Village in 2019 was very low (less than 5%). This situation is motivated by the phenomenon of child deaths after immunization, information that doubts the halal content of vaccines. Objective: to determine the perception of the community of Benda Kerep village towards providing immunizations to children in the working area of the Sitopeng Community Health Center, Cirebon City. Method: qualitative research using a phenomenological approach involving seven participants. Data was collected using the FGD process and field notes. Data analysis uses the Colaizzi method. Results: There are six themes including: perceptions about the immunization program, reasons for refusing and accepting immunization, husband's response to immunization, implementation of immunization activities, impact of immunization and efforts to deal with sick children, views on the attitudes and behavior of health workers. Conclusion: The perception of the people of Kampung Benda Kerep is still not good regarding the provision of immunizations. A special strategy is needed in implementing routine immunization programs by increasing the involvement of regional leaders, health workers, TOMA, TOGA, community organizations and various other parties so that people do not hesitate to accept the immunization program.